2021
DOI: 10.15252/embr.202051913
|View full text |Cite
|
Sign up to set email alerts
|

Loss of enteric neuronal Ndrg4 promotes colorectal cancer via increased release of Nid1 and Fbln2

Abstract: The N‐Myc Downstream‐Regulated Gene 4 ( NDRG4 ), a prominent biomarker for colorectal cancer (CRC), is specifically expressed by enteric neurons. Considering that nerves are important members of the tumor microenvironment, we here establish different Ndrg4 knockout ( Ndrg4 −/− ) CRC models and an indirect co‐culture of primary enteric nervous system (ENS) cells and intestinal organoids to identify whether the ENS, via NDRG4, affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 71 publications
0
12
0
Order By: Relevance
“…The protein sequences encoded by this family have a 52-65% homology and are highly conserved in the evolution of various species (43), with α/β hydrolase folding. Previously, researchers have identified NDRG4 promoter CpG island methylation as a potential and one of the most accurate marker for CRC detection (44), and this has been verified by an independent study (45).…”
Section: Screening and Early Detection Markersmentioning
confidence: 72%
“…The protein sequences encoded by this family have a 52-65% homology and are highly conserved in the evolution of various species (43), with α/β hydrolase folding. Previously, researchers have identified NDRG4 promoter CpG island methylation as a potential and one of the most accurate marker for CRC detection (44), and this has been verified by an independent study (45).…”
Section: Screening and Early Detection Markersmentioning
confidence: 72%
“…Interestingly, ADAMTS-12 was found to promote tumor development in breast cancer cells lacking FBLN2 by regulating metalloproteinase ( Fontanil et al, 2014 ). In contrast, another study found that FBLN2 promoted tumor growth by interacting with activated β integrin receptor in CRC ( Vaes et al, 2021 ). Consistent with the above finding, high expression level of these two genes ( FBLN2 and HTRA3 ) was linked to worse prognosis in colon cancer ( Figures 9E,F ), and FBLN2 was found to be significantly differentially expressed in CC ( Figure 9H ).…”
Section: Discussionmentioning
confidence: 95%
“…N-Myc Downstream-Regulated Gene 4 (NDRG4), expressed within nervous system structures throughout the body, but predominantly studied in the brain and heart, was proven to be expressed explicitly in enteric neurons in a study using tissues from NDRG4 wild-type, heterozygous, and knockout mice and humans; immunoreactivity was restricted to the enteric nervous system (ENS) [ 58 ]. A recent study aiming to identify whether the ENS, via NDRG4, affects intestinal tumorigenesis showed that Ndrg4 knockdown in CRC models and in an indirect co-culture of primary enteric nervous system (ENS) cells was associated with enlarged intestinal adenoma development—the organoid growth being boosted by the Ndrg4−/− ENS cell secretome—the ENS, via loss of Ndrg4, being involved in colorectal pathogenesis [ 59 ].…”
Section: Resultsmentioning
confidence: 99%